2001
DOI: 10.1111/1467-6451.00162
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Decision‐making at an Internet Shopbot: Brand Still Matters

Abstract: Internet shopbots compare prices and service levels at competing retailers, creating a laboratory for analysing consumer choice. We analyse 20,268 shopbot consumers who select various books from 33 retailers over 69 days. Although each retailer o¡ers a homogeneous product, we ¢nd that brand is an important determinant of consumer choice. The three most heavily branded retailers hold a $1.72 price advantage over more generic retailers in head-to-head price comparisons. In particular, we ¢nd that consumers use b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
265
4
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(279 citation statements)
references
References 23 publications
7
265
4
3
Order By: Relevance
“…Furthermore, we also show that price dispersion in the electronic market is significantly lower than in the traditional market. This result is consistent with some work in the earlier literature, all of which used posted prices, supporting the theoretical argument that search cost in electronic markets is lower than that in traditional markets (Bakos 1997, Smith and Brynjolfsson 2001, Smith 2001. Given that our findings are different from those in many earlier studies, we point out that our findings should be interpreted in light of the differences in the research settings.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, we also show that price dispersion in the electronic market is significantly lower than in the traditional market. This result is consistent with some work in the earlier literature, all of which used posted prices, supporting the theoretical argument that search cost in electronic markets is lower than that in traditional markets (Bakos 1997, Smith and Brynjolfsson 2001, Smith 2001. Given that our findings are different from those in many earlier studies, we point out that our findings should be interpreted in light of the differences in the research settings.…”
Section: Introductionsupporting
confidence: 90%
“…The summary shows that published price dispersion varies greatly, from as low as 4% to as high as 57%. 2 Earlier theoretical and empirical work suggests that price dispersion may result from bundling products with services Smith 2000, Baye et al 2004); differences in brand, reputation, and trust across sellers , Baye et al 2006, Chen and Hitt 2003; retailer heterogeneity (Smith and Brynjolfsson 2001, Baylis and Perloff 2002, Bailey et al 1999; product heterogeneity (Baye et al 2006); price discrimination (Clemons et al 2002); randomized pricing strategies by firms (Varian 1980, Chen and Hitt 2003, Ghose et al 2007; interaction between retailer and market characteristics (Venkatesan et al 2007), multiple channel operations (Ancarani andShankar 2004, Pan et al 2003b); and differences in vendor price format such as everyday low prices (EDLP) (Sin et al 2007, Chellappa et al 2007.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Athey and Meidan (2011) and Athey and Nekipelov (2011) are important papers on the analysis of user behavior in the paid results. Previous research has indicated that CTRs can increase markedly for results placed at the top of a results page compared to other ranks and pages (Smith and Brynjolfsson 2001;Xu and Kim 2008;Ghose and Yang 2009. Of these studies, Xu and Kim (2008) is based on a small-sample laboratory experiment, and Xu and Kim (2008) uses data on paid search from an advertiser.…”
Section: Introductionmentioning
confidence: 99%
“…This is unobservable for Geizhals.at and thus for us. Therefore, following Smith and Brynjolfsson (2001) and Bai (2004), we use the concept of last-click-through (LCT) as a proxy for the purchasing decision. If a customer is searching for a product, she might meander around different web sites, comparing characteristics of the shops, but she will finally settle for the preferred shop and buy there online.…”
Section: Data and Prevalence Of Price Pointsmentioning
confidence: 99%